2012
DOI: 10.1177/0956797611434746
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Priming From Crowded Words

Abstract: Vision in a cluttered scene is extremely inefficient. This damaging effect of clutter, known as crowding, affects many aspects of visual processing (e.g., reading speed). We examined observers' processing of crowded targets in a lexical decision task, using single-character Chinese words that are compact but carry semantic meaning. Despite being unrecognizable and indistinguishable from matched nonwords, crowded prime words still generated robust semantic-priming effects on lexical decisions for test words pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 40 publications
6
58
1
1
Order By: Relevance
“…In support of these findings, another recent study found that illusory contour formation, a process that relies on the configuration of the inducer stimuli, can also survive crowding of the individual inducers (Lau and Cheung, 2012) [but see (Banno and Saiki, 2012) for data suggesting that size information does not survive crowding]. Further, crowded objects can unconsciously influence behavior by priming subsequent responses (Faivre and Kouider, 2011; Yeh et al, 2012) and biasing preferences (Kouider et al, 2011). …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In support of these findings, another recent study found that illusory contour formation, a process that relies on the configuration of the inducer stimuli, can also survive crowding of the individual inducers (Lau and Cheung, 2012) [but see (Banno and Saiki, 2012) for data suggesting that size information does not survive crowding]. Further, crowded objects can unconsciously influence behavior by priming subsequent responses (Faivre and Kouider, 2011; Yeh et al, 2012) and biasing preferences (Kouider et al, 2011). …”
Section: Introductionmentioning
confidence: 88%
“…Thus, while the general idea of involuntary pooling captures many aspects of crowding and likely plays a role, over integration is not the whole story. Other models of crowding, including substitution (Wolford, 1975; Chastain, 1982) and contrast-gain or masking based models (Krumhansl and Thomas, 1977; Chastain, 1981; Petrov and Popple, 2007) are not more successful; they similarly require that information about crowded objects is lost or substantively modified, a prediction that has been overturned (Faivre and Kouider, 2011; Fischer and Whitney, 2011; Kouider et al, 2011; Lau and Cheung, 2012; Yeh et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The semantic representations of words are quickly activated (Cave & Batty, 2006), even without awareness (Yang & Yeh, 2011;Yeh, He, & Cavanagh, 2012) and evaluated in terms of the strength of their emotional valences (e.g., threat; LeDoux, 1996;Mathews & Mackintosh, 1998). Words associated with negative emotion tend to receive attentional priority (Mathews & Mackintosh, 1998).…”
Section: Emotion-specific Accountsmentioning
confidence: 99%
“…In one recent study, Yeh et al (2012) rendered unrecognizable a single-character Chinese word that was presented in the periphery by surrounding it with other non-words. The crowded target word was perceived within the jumble as 'something there', though it could not be identified and could not be classified as either a word or a non-word.…”
Section: Priming Under Visual Crowdingmentioning
confidence: 99%